2002
DOI: 10.1124/jpet.302.1.153
|View full text |Cite
|
Sign up to set email alerts
|

α4β74β1Dual Integrin Antagonists Block α4β7-Dependent Adhesion under Shear Flow

Abstract: The ␣ 4 integrin, ␣ 4 ␤ 7 , plays an important role in recruiting circulating lymphocytes to the gastrointestinal tract, where its ligand mucosal addressin cell adhesion molecule-1 (MAd-CAM-1) is preferentially expressed on high endothelial venules (HEVs). Dual antagonists of ␣ 4 ␤ 1 and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Mouse anti-human CD29, HUTS-21(PE), isotype control (mouse IgG2a κ PE) clone G155-178 were purchased from BD Biosciences (San Jose, CA) and used according to manufacturer's instructions. 16 was synthesized by Dr. Wei Wang (Department of Chemistry, University of New Mexico). Two recently identifi ed VLA-4 ligands 3-(adamantane-1-carbonylamino)-3-(4-ethoxyphenyl) propanoic acid and 3-(adamantane-1-carbonylamino)-3-(4-propoxyphenyl) propanoic acid (SID: 14732971, CID: 5197400; and SID: 14732972, CID: 4329131) were from NIH molecular libraries small molecule repository (NIH MLSMR) (http://pubchem.ncbi.nlm.nih.gov/) curated by BioFocus/ DPI (South San Francisco, CA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mouse anti-human CD29, HUTS-21(PE), isotype control (mouse IgG2a κ PE) clone G155-178 were purchased from BD Biosciences (San Jose, CA) and used according to manufacturer's instructions. 16 was synthesized by Dr. Wei Wang (Department of Chemistry, University of New Mexico). Two recently identifi ed VLA-4 ligands 3-(adamantane-1-carbonylamino)-3-(4-ethoxyphenyl) propanoic acid and 3-(adamantane-1-carbonylamino)-3-(4-propoxyphenyl) propanoic acid (SID: 14732971, CID: 5197400; and SID: 14732972, CID: 4329131) were from NIH molecular libraries small molecule repository (NIH MLSMR) (http://pubchem.ncbi.nlm.nih.gov/) curated by BioFocus/ DPI (South San Francisco, CA).…”
Section: Methodsmentioning
confidence: 99%
“…2C) is described in the literature as a potent ligand that blocks VLA-4 binding to vascular cell adhesion molecule 1 (VCAM-1). 11,16,24 Compounds D and E ( Fig. 2D and 2E) are two novel VLA-4 ligands discovered in a high-throughput screen at the University of New Mexico Center for Molecular Discovery (http://pubchem.ncbi.nlm.nih.gov, AID: 529, 702).…”
Section: Homology Modeling and Dockingmentioning
confidence: 99%
“…TR14035 (Fig. 1) has been reported to potently inhibit both ␣ 4 ␤ 1 and ␣ 4 ␤ 7 Sircar et al, 1999a,b;Egger et al, 2002), and this was confirmed (Table 1).…”
Section: Downloaded Frommentioning
confidence: 55%
“…Compound 2, a recently described ␣ 4 ␤ 1 antagonist (Hagmann et al, 2001), and compound 3, a structurally related analog, inhibited binding to both ␣ 4 ␤ 1 and ␣ 4 ␤ 7 (Table 1). An inactive analog, compound 4 (Hagmann et al, 2001;Egger et al, 2002), did not inhibit binding when tested at concentrations up to 100 M, demonstrating the importance of specific structural features to the activities of compounds 1, 2, and 3 (Kopka et al, 2002; Table 1). TR14035 (Fig.…”
Section: Downloaded Frommentioning
confidence: 99%
See 1 more Smart Citation